The impact of frailty in major trauma in older patients. Issue 7 (July 2020) - Pecheva, M; Phillips, M; Hull, P; Carrothers A, O'Leary R; Queally, JM
Highlights: This is the first study that specifically assesses the impact of frailty on outcomes in older patients who experience major trauma. High frailty is associated with high mortality rates at both hospital discharge and one year post injury. High frailty is associated with a higher rate of serious complications following polytrauma including unplanned intubation, infection and renal failure. Intermediate and high frailty patients were more likely to be discharged to an unfavourable discharge destinations. This study provides valuable information for future healthcare provision for Major Trauma Centres in the setting of polytrauma in older patients. ABSTRACT: As our population ages and increasing numbers of older patients experience major trauma it is important to understand factors that influence outcomes in this patient cohort. The aim of this study is to assess the impact of frailty in older patients who experience major trauma (Injury Severity Score (ISS) greater than 15). A retrospective cohort review using the national trauma registry data (Trauma Audit and Research Network) and an institutional database was carried out on all patients aged 60 years or older with an ISS> 15 who were treated at the regional Major Trauma Centre from 2014 to 2017 following major trauma. Frailty was assessed using the modified frailty index (mFI). Outcomes assessed included mortality, complications, hospital stay, functional outcome and discharge destination. 819 patients were included in the study. The most common mechanism of injury was fall from a height less than 2m (57.4%). 412 (51.3%) patients had a low frailty score, 280 (35%) had an intermediate frailty score and 110 (14%) had high frailty score. Increased frailty was associated with increased mortality at discharge (18.7%, 14.6% and 26.4% for low, intermediate and high frailty groups) and at one year (26.2%, 35.2% and 51%, respectively). Other predictors of mortality included male sex, age >90 years and the occurrence of a serious complication. Increasing frailty was also associated with an increased risk of serious complications including unplanned intubation, infection and progressive renal failure, and discharge to a destination other than home. This is the first study that has delineated the impact of frailty in older patients who experience major trauma and provides important information for patients, their families and healthcare providers. Future studies should focus on identifying care pathways that counteract the impact of frailty in this setting.